Nutritional characterization of Detarium microcarpum Guill. & Perr., seeds used as a soup thickener in Bayelsa State - Akhigbe, Esther O.; Etukudoh, Mbosowo; Ezeoke, Kelechi J. (Nigerian Journal of Pharmaceutical and Applied Science Research, 2024)
Background: This research was carried out to determine the nutritional and phytochemical constituent of Detarium microcarpum seeds commonly known as ‘ofor’ used in Otuoke, Bayelsa State and Environs. Methods: Fresh fruits of Detarium microcarpum were collected from secondary forest in Otuoke and identified. Dry ground seeds were analyzed for mineral elements, proximate composition and phytochemical constituent. Mean and standard error were calculated for the data collected. Results: Data collected revealed that seeds of D. microcarpum are a rich source of essential minerals like magnesium (57.20 mg/100 g) and potassium (46.30 mg/100 g), which are vital for health and functionality of human heart. However, the content of manganese was relatively low (0.16 mg/100 g). Values for proximate content showed high carbohydrate content (63.37%), crude proteins (17.21%) and crude ash (2.81%) which make the seeds a source of balance meal. Furthermore, low water content (8.64%) was observed, which is essential for storage. The results obtain for phytochemical analysis revealed the presence of alkaloids (1.50 mg/ 100 g), tannins (2.97 mg/100 g), flavonoids (1.22 mg/100 g), saponins (1.02 mg/100 g), oxalates (0.53 mg/100 g) and phytates (0.74 mg/100 g). Conclusion: The result obtained in this study demonstrated that seeds of Detarium microcarpum are a good source of vital nutrients and bioactive compounds which can enhance planetary health.